Meningkatkan Prestasi Belajar melalui Model Project Based Learning Pokok Bahasan Sistem Ekskresi Manusia pada Kelas XI MIA 2 SMA Negeri 2 Bungku: Meningkatkan Prestasi Belajar melalui Model Project Based Learning Pokok Bahasan Sistem Ekskresi Manusia pada Kelas XI MIA 2 SMA Negeri 2 Bungku - Kaharudin, La Ode; -, Bardin; -, Marhumi (Universitas Muslim Buton, 2022)
Project based learning is a learning model that is student-centered, project-oriented and the results of the project are presented by students. The purpose of this study was to describe the application of the project based learning model and analyze the increase in student understanding after the project based learning model was applied. This research was conducted in class XI MIA 2 SMA Negeri 2 Bungku, totaling 30 students for the 2021/2022 academic year. The test results show the Teaching Completeness Criteria (TCC) on the subject of the human excretory system, in the first cycle 70% or as many as 21 students meet teaching mastery and 30% or 9 students do not meet teaching completeness. Cycle II there are teaching completeness is 85% or as many as 26 students meet teaching completeness and incomplete there are 15% or 4 students do not meet teaching completeness. Cycle III there is a teaching completeness is 95% or 29 students meet teaching completeness and 5% incomplete or 1 student does not meet teaching completeness. This increase in learning achievement is marked by an increase in each cycle from cycles I, II and III.